An Improved Chevron Configuration for the Detection of Magnetic Field Vectors - Mohd Ali, Borhanuddin (Universiti Putra Malaysia Press, 1993)
A modified version of Chevron type Magnetoresistive Recording Heads (MRH) sensor is described. Two shielded ferromagnetic thin-film vertical-type MRH are biased at the linear region simultaneously using a small piece of permanent magnet chip. The biasing rotates the magnetisation vector Ms of each MRH . through 4S· with respect to their respective current vectors J resulting in an effective Chevron orientation of 90·. This configuration is shown to be most effective to detect field vectors in applications such as non-destructive detection of grain structures and loss variation in electrical steels, and in packing more bits of information in magnetic disc storage.